2020
DOI: 10.1021/acsami.0c01222
|View full text |Cite
|
Sign up to set email alerts
|

Shape and Orientation Controlled Hydrothermal Synthesis of Silicide and Metal Dichalcogenide on a Silicon Substrate

Abstract: Shape-controlled MoS 2 has been grown directly on a silicon substrate, for the first time, with the use of a facile hydrothermal synthesis approach. The growth morphology is dependent on the substrate orientation. Square, hexagonal, and triangular patterns of MoS 2 are grown on Si(100), Si(110), and Si(111), respectively. Detailed studies reveal that Mo silicide is formed at the initial stage, and the formation of silicide patterns is dictated by the different surface energies of Si(100), Si(110) and Si(111). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…39 Consequently, these methods have garnered significant interest for synthesising TMDs, LDHs, and their respective composites. 40,41 As shown in Fig. 1, flower-like structures are often formed using the hydrothermal method.…”
Section: Hydrothermal and Solvothermal Synthesismentioning
confidence: 99%
“…39 Consequently, these methods have garnered significant interest for synthesising TMDs, LDHs, and their respective composites. 40,41 As shown in Fig. 1, flower-like structures are often formed using the hydrothermal method.…”
Section: Hydrothermal and Solvothermal Synthesismentioning
confidence: 99%
“…[ 243 ] The hydrothermal/solvothermal process typically requires a long reaction time (e.g., 48 h) for synthesizing 2D materials. [ 143,244,245 ] To address this issue, Yan et al [ 233 ] reported a facile and efficient microwave‐assisted solvothermal method for the synthesis of WS 2 nanosheets in NMP, using cheap tungsten hexachloride (WCl 6 ) and elemental S as the starting materials. Compared to the long synthesis time of the traditional hydrothermal method, the microwave‐assisted solvothermal reaction is considerably faster (within 8 hours) with a high yield (>90%) and satisfactory reproducibility.…”
Section: The Preparation Of 2d Materialsmentioning
confidence: 99%
“…Recently, ultra-doping of semiconducting materials such as MoO 3 has shown great promise in producing near IR and visible light plasmon resonance. , The plasmonic behaviors in these quasi-metallic materials can be tunable, driven by the concurrently injected charge carriers during the doping processes. Consequently, facile and controlled synthesis of plasmonic metal oxides is one of the most critical criteria to realize many applications based on these versatile materials. ,, The conventional synthesis of this type of plasmonic materials is mainly via the reduction intercalation of MoO 3 with Zn/HCl solutions or using noble metal-coated MoO 3 in the presence of H 2 gas through a spill-over process. The synthesis relies on harsh solvents, elevated temperature or pressure, and noble metals, which are not environmentally friendly and less cost-effective . Other techniques include solar light irradiation to achieve the separation of photo-generated electrons and hole pairs, consequently producing charges to dope the 2D MoO 3 . , However, MoO 3 has a band gap of ∼3.2 eV and can only be excited under the optical wavelengths of ∼387 nm.…”
Section: Introductionmentioning
confidence: 99%
“…23−25 The synthesis relies on harsh solvents, elevated temperature or pressure, and noble metals, which are not environmentally friendly and less cost-effective. 26 Other techniques include solar light irradiation to achieve the separation of photogenerated electrons and hole pairs, consequently producing charges to dope the 2D MoO 3 . 27,28 However, MoO 3 has a band gap of ∼3.2 eV and can only be excited under the optical wavelengths of ∼387 nm.…”
Section: Introductionmentioning
confidence: 99%